2003
DOI: 10.1084/jem.20020737
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Heavy Chain Rearrangement

Abstract: The chronic graft-versus-host (cGVH) reaction results in a syndrome that closely resembles systemic lupus erythematosus (SLE). It is induced in nonautoimmune mice by the transfer of alloreactive T cells. The availability of anti-DNA transgenes allows us to study the genetic origins of autoantibodies in this model. We induced cGVH in two anti-DNA H chain site-directed transgenic mouse strains. This resulted in clonal expansion and selection of specific mutations in the anti–double-stranded (ds) DNA B cell popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Like any recombination process, V H replacement is a random process that can generate non-functional IgH genes or IgH genes encoding autoreactive antibodies. Previous studies have shown that V H replacement products generated through replacing the knocked-in anti-DNA IgH genes can produce high affinity anti-DNA antibodies during chronic graft-versus-host (cGVH) response [56]. Theoretically, after V H replacement recombination, the newly generated IgH genes should be subjected to strict negative selection again to eliminate B cells expressing autoreactive BCRs.…”
Section: Discussionmentioning
confidence: 99%
“…Like any recombination process, V H replacement is a random process that can generate non-functional IgH genes or IgH genes encoding autoreactive antibodies. Previous studies have shown that V H replacement products generated through replacing the knocked-in anti-DNA IgH genes can produce high affinity anti-DNA antibodies during chronic graft-versus-host (cGVH) response [56]. Theoretically, after V H replacement recombination, the newly generated IgH genes should be subjected to strict negative selection again to eliminate B cells expressing autoreactive BCRs.…”
Section: Discussionmentioning
confidence: 99%
“…In the GVHD model, no foreign ag is administered, therefore only self-ag reactive B cells will encounter endogenous signal 1 and become autoantibody secreting cells. IgG anti-ssDNA ab appear early (days 10–14) [17] and after this initial B cell expansion a second ag-driven phase ensues at >1 month of disease [15] characterized by detection of lupus-specific auto-antibodies not seen earlier e.g., anti-dsDNA, Sm, chromatin [18,19] and poly(ADP-ribose) polymerase-1 (PARP-1) depending on the P→F1 combinations used [20]. Clinical renal disease becomes demonstrable at approximately 2 months.…”
Section: Lupus Development In the Parent-into-f1 (P→f1) Model Of Lmentioning
confidence: 99%
“…Another possibility is that the editing defect in B6.Aec1/2 mice is significant, but that its effects on the 56R transgene are insufficient to limit autoreactivity, even in wild type mice. Indeed, B6.56R and even B6 mice spontaneously break tolerance to dsDNA, so clearly editing is not a panacea (49, 61, 70). Even when antibody light chains are edited in B6.56R mice, most do not fully negate the autoreactive specificity of the 56R heavy chain.…”
Section: Discussionmentioning
confidence: 99%